2022
DOI: 10.21203/rs.3.rs-1645920/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromosome-level genome of Capitulum mitella reveals an ancient whole-genome duplication event and intertidal adaptation of barnacles

Abstract: Barnacles are the only sessile crustaceans inhabiting intertidal zone, an extremely stressful environment for sessile organisms. Herein, we report the chromosome-level genome of a stalked barnacle, Capitulum mitella, which is a dominant intertidal cirripede of the west Pacific Ocean coast. After comprehensive comparative genomic analyses, it is first time to find an ancient whole-genome duplication (WGD) event that preceded the divergence of Lepadomorpha and Sessilia approximately 237 million years ago. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Mollusc ALPs were mostly intact but lacked such specific motif of barnacles. This specific motif arose from the ancestral ALPs and thus evolved before the divergence of the two kinds of barnacles (greater than 237 MYA) [22]. Surprisingly, we found that this motif remained highly conserved, and 52 of the 55 amino acid sites were identical (100%) among 35 ALPs of the two barnacles, despite their distant evolutionary divergence.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…Mollusc ALPs were mostly intact but lacked such specific motif of barnacles. This specific motif arose from the ancestral ALPs and thus evolved before the divergence of the two kinds of barnacles (greater than 237 MYA) [22]. Surprisingly, we found that this motif remained highly conserved, and 52 of the 55 amino acid sites were identical (100%) among 35 ALPs of the two barnacles, despite their distant evolutionary divergence.…”
Section: Resultsmentioning
confidence: 88%
“…The protein-coding genes of nine arthropods and four molluscs were collected from NCBI genome database and used for gene family analysis, including Capitulum mitella (PRJNA753937 [23]), Amphibalanus amphitrite (PRJNA751628) [24], Eulimnadia texana (PRJNA352082) [25], Eurytemora affinis (PRJNA423276) [26], Tigriopus californicus (PRJNA237968) [27], Armadillidium vulgare (PRJNA501402) [28], Parhyale hawaiensis (PRJNA306836) [29], Litopenaeus vannamei (PRJNA438564) [30], Procambarus virginalis (PRJNA356499) [31], Mizuhopecten yessoensis (PRJNA390633) [32], Crassostrea gigas (PRJEB35351) [33], Modiolus philippinarum (PRJNA328544) [34] and Octopus bimaculoides (PRJNA305125) [35]. Gene family clustering was performed on the protein-coding genes of nine arthropods using O rtho F inder .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations